KOMPARASI TINGKAT KEASAMAN PADA KOPI ARABIKA, KOPI LUWAK DAN KOPI HASIL IRADIASI BATAN - Jepri Sutanto; Musaddiq Musbach; Achmad Suntoro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Coffee is one of the most consumed beverages in the world. In this experiment will determine the level of acidity in Arabica coffee (Toraja), Civet coffee (Gayo), and irradiation coffee from National Nuclear Energy Agency (BATAN). The difference of acidity before and after irradiation is carried out by measuring the cup of coffee at temperature 600C to 250C using pH meter PM 6-Dr.A.KUNTZE GmbH. Irradiator technology is used to eradicate the insects, inactivate pathogenic microorganisms, and to eliminate all other bacterial pathogens in coffee. In accordance with the recommendations PERMENKES 701/Menkes/PER/VIII/2009, CODEC STAN 106-1983, REV.1-2003, and SNI 01.2907:2008, 10 kGy doses is conducted to irradiate of coffee. Differentiation of the acidity levels before and after irradiation for arabica coffee and civet coffee are 2.76% and 3.09%. The results of the measurement (4 samples), the acidity of Arabica coffee (Toraja) 5.07, Civet coffee (Gayo) 4.84, irradiation coffee of Arabica (Toraja) 5.21, irradiation coffee of civet (Gayo) 4.99. From the measurement results showed that irradiation coffee from BATAN, the level of acidity is lower than before irradiation.Keywords: coffee, acidity, pH meter, irradiation.